Co-Design and Development of Digital Health Solution for Informal Alzheimer’s Caregivers - Maria Maia Almeida; Carla Sílvia Fernandes; Marta Campos Ferreira (Alzheimer Disease & Associated Disorders, 2026)
Introduction: Alzheimer disease (AD) imposes significant cognitive, emotional, and practical challenges on individuals and their caregivers. Informal caregivers, often family members, assume a central role in managing complex care routines, frequently with limited support. Digital tools offer promising avenues for addressing these challenges, yet existing solutions often lack integration, personalization, or user-centered design. Methods: This study presents the design, development, and validation of AlzCare, a digital health solution developed using a user-centered design (UCD) methodology. The needs assessment involved 52 survey respondents and 6 in-depth interviews with caregivers and healthcare professionals. Based on this, a prototype was developed integrating modules for health monitoring, cognitive stimulation, task management, and caregiver support. Usability and functionality were evaluated through testing with 25 participants using task-based interaction, semistructured interviews, and the System Usability Scale (SUS). Results: The solution received highly positive feedback regarding usability, relevance, and emotional resonance. The SUS yielded a mean score of 90.9, indicating “Best Imaginable” usability. Users valued features such as daily health tracking, the “Who Am I?” reminiscence tool, and the caregiver support section. Suggestions included automating data entry and integrating wearables. Discussion: AlzCare demonstrates how digital technologies developed through participatory approaches can support informal dementia caregiving across practical and emotional dimensions. Future work will focus on broader clinical integration, automation, and longitudinal validation in real-world settings. The findings reinforce the value of accessible, holistic digital tools in advancing dementia care within telemedicine ecosystems.